Doppler ultrasound in standing position is superior to demonstrate nutcracker phenomenon in children with varicocele - Tekin, Ali; İsmailoglu, Eren (Journal of Surgery and Medicine, 2021)
Background/Aim: The nutcracker phenomenon refers to the entrapment of the left renal vein between the superior mesenteric artery and the aorta. It is named nutcracker syndrome if accompanied by symptoms such as flank pain, hematuria, proteinuria, and varicocele. This study aimed to determine the rate of nutcracker phenomenon in children with varicocele by left renal vein Doppler US measurements in standing and supine positions. Methods: The hospital records of patients admitted to our clinic with grades 2 and 3 left varicocele between 2017 and 2019 were reviewed retrospectively. Demographic data, BMI values, blood pressure values, and urinalysis results of the patients were recorded. The diameter and the peak velocity (PV) of the left renal vein were measured at the level of the hilus and in the aortomesenteric part, both in supine and standing positions by Doppler ultrasonography (US). Results: Twenty-six cases were included in the study. No additional pathology was found other than varicocele. The diameter of the aortomesenteric part of the renal vein decreased, the hilar part of the renal vein increased, and the rate and the diameter ratio increased at the standing position. The incidence of the nutcracker phenomenon was 42.3-57.7% with different thresholds in the supine position, and 88-96.2% in the standing position. Conclusion: Doppler ultrasonography in the standing position is superior to that performed in the supine position in detecting the nutcracker phenomenon in patients with varicocele.